Comparing temporal characteristics of slug flow from tomography measurements and video observations. (December 2021) - Olbrich, Marc; Hunt, Andrew; Leonard, Terri; van Putten, Dennis S.; Bär, Markus; Oberleithner, Kilian; Schmelter, Sonja
Abstract: In industrial operations, the slug flow pattern can lead to serious problems, that are mostly caused by the liquid slugs of the flow. Hence, a detailed description of the slug flow pattern is of special interest. In this context, the temporal flow characteristics that are derived from high-speed video observations of the flow, are compared to tomography measurements. For this, the liquid level time series as well as the temporal slug characteristics of two different slug flow experiments are considered. It is shown that the liquid level time series from the video observations are systematically overestimated, but the slug dynamics are in good agreement.